An Integrated Reforestation, Conservation and Sustainable Livelihood Program for Kanawan Aytas in Morong, Bataan: A Science-Based Community Empowerment Model - Motin, Borromeo; Mani, Merian; Sespene, Jeter (Romblon State University Research Journal, 2011)
This paper aims to share lessons learned in the implementation of the science-based community development program entitled “Establishment of Integrated Reforestation, Conservation and Sustainable Livelihood Program for Kanawan Aytas in Morong, Bataan-Philippines.” This program provides Ayta community the opportunity to demonstrate their traditional knowledge in preserving and conserving remaining resources and helps them to develop a culture-based sustainable livelihood program. Particularly, this paper is on the interplay of social science aspects and synergism of scientific and traditional knowledge in the implementation of the program. It also tackles the methods and processes developed and used by the community to nurture the sense of community ownership and the community-based management mechanisms as strategies to strengthen their capacity and to promote empowerment of the community.